Indonesian lexical bundles in research articles: Frequency, structure, and function - Budiwiyanto, Adi; Suhardijanto, Totok (Indonesian Journal of Applied Linguistics, 2020)
Recent studies show that lexical bundles in English are pervasively found in academic discourse. In addition, the characteristics of lexical bundles found vary and differ across registers and genres. Nevertheless, it is still interesting to carry out in languages other than English. This study aims to discover the characteristics of Indonesian lexical bundles that cover frequency, structure, and function in research articles. This study adopted a mixed-method. Identification of the lexical bundle was carried out using WordSmith 7.0 on a corpus comprising 3,125,546 words, taken from 1126 texts, and consisting of six disciplines. With a frequency threshold of 40 per million words and a minimum distribution of 5 texts, 197 lexical bundles have been obtained, consisting of three- to six-word bundles with a total occurrence of 51,813 times. In terms of structure, the incomplete structure is dominating the bundles by 78.7%, with a total frequency of occurrence 38,749 times. This research finds that the pattern of lexical bundles can be classified into five types: noun-based, prepositional-based, verb-based, adjective-based, and clause-based bundles. Lexical bundles in research articles are generally clause-based (49.2%). This indicates that Indonesian lexical bundles vary in structure. The use of clause fragments and passive verbs are the main features in this genre. In terms of the discourse function, research-oriented bundles are the functions that are commonly used, while participant-oriented bundles are the least. Each discourse function has its own structural characteristics. It is also found that one lexical bundle can have two functional categories. These findings contribute to a better understanding of the characteristics of written academic discourse. From the pedagogical point of view, the ï¬ndings can be used as learning material for both native and non-native speakers.